Approaches to Strengthening Flood Risk Management - Jianting Cao; Zhongnan Zhao; Ziqiang Xing (中国工程科学)
Flood is one of the most serious natural disasters, and China's flood control policies have transitioned from reducing disaster losses to mitigating disaster risks. Research on the driving factors and management approaches of flood risks will provide technical support for formulating and implementing flood control strategies, with great significance for adopting diversified measures to improve flood risk management and reduce flood losses. Based on the research progresses relating flood risk management in China and abroad, this study elucidates the major components or driving factors of flood risks, explores the major approaches to reducing flood risks, and analyzes the environment for effectively implementing flood risk management. The results indicate: (1) Flood risks depend not only on the hazardous flood, but also on the exposure and vulnerability of the economy and society threatened by flood; (2) the risk of flood disasters cannot be completely eliminated, but can be regulated to an acceptable level by implementing a series of measures at different stages of prevention, preparedness, emergency response, and post disaster reconstruction; (3) approaches for flood risk management include improving the planning of flood risk management, strengthening spatial plan and management with inclusion of flood risk information, improving the flood control structure system, and enhancing flood emergency preparedness, response, and recovery capabilities; and (4) improving policies and regulations, effective coordination mechanisms, and promoting participation of the whole social can enable the effective implementation of flood risk management. The following suggestions are further proposed: (1) strengthening flood risk assessment, determining the acceptable flood disaster risks, and improving the flood control standards system; (2) diversifying approaches and measures tailored to different conditions to reduce flood risks; and (3) enhancing the whole society's awareness of flood risks and promoting their participation in flood risk management.